Impelentasi pencatatan laporan keuangan Usaha Kecil dan Menengah di Kabupaten Timor Tengah Utara - Kase, Marce Sherly; Dewi Redjo, Paulina Rosna (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
Financial management problems are problems that are often faced by small and medium businesses. Accounting practices are solutions that can be applied to make it easier to apply the accounting records used. This study aims to determine the application of accounting carried out by small and medium enterprises in North Central Timor Regency, which is a leading sector. The analysis technique uses descriptive qualitative analysis, using an interpretive paradigm. Data was collected through in-depth interviews with 28 informants to ensure that the practice of implementing financial records had been presented properly and correctly, and then referred to the theory of accounting systems related to generally accepted financial records. There are two forms of accounting practices in small and medium enterprises, namely, accounting, which is only practiced in memory, and making several accounting records to compile balance sheets and L/R financial statements. The benefits of these two forms of accounting are limited to controlling several business activities. The results of field observations based on interviews show that as many as 85% of SMEs in TTU Regency in the trade and automotive business sectors still do not have the ability to present complete and accurate financial information.